Joshua - Girzone, Joseph F. (Macmillan, 1987)
"When Joshua moves to a small cabin on the edge of town, the local people are first mystified, then confused by his presence. A quiet and simple man, Joshua appears to seek nothing for himself. He supports himself solely by carpentry and woodworking; and he charges very little for his services. A statue of Moses he carves for a synagogue causes amazement and consternation. His carvings of the apostle Peter [for the town's churches] surprise the pastors and members....Neither is what they expected. Both are haunting. What sort of a person is Joshua? How can the townspeople explain a few rumors about him?....The woodcarver disturbs some of his neighbors. While he quietly and lovingly urges all around him to break down the walls that separate them, there are others who are frightened of him...."